ОБҐРУНТУВАННЯ ПАРАМЕТРІВ ТЕХНОЛОГІЇ ЗАКЛАДАННЯ ПОРОДИ У ВИРОБЛЕНИЙ ПРОСТІР ОЧИСНОГО ВИБОЮ В УМОВАХ ПЛАСТА D4 ПРАТ "ШУ "ПОКРОВСЬКЕ" - Руських, Владислав; Шумов, Андрiй; Тимошенко, Євген; Передерій, Наталія (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2025)
The purpose of the work is to substantiate the parameters of the mining technology with the rock left over from preparatory workings in the working space of the face. Methodology and scientific approaches the tasks set were solved by a comprehensive research method, including analysis and generalization of literary and patent sources, data processing on the physical and mechanical properties of rocks. Novelty is methodology for determining the rational parameters of the development system with the placement of rocks from the preparatory workings into the working space of the face was developed and the regularity of changes in the width of the rock strip that is placed in the working space of the face was established, depending on the cross-sectional area of the preparatory workings and the thickness of the formation. Possibility of using the results the results of the work form the basis for designing coal deposits with rock injection into the mined-out space in the working face in the conditions of the d4 seam of Pokrovske Mining Company. Practical value is to develop a methodology for determining the rational parameters of coal seam mining, which allows for resource saving during mining operations. Originality/value. A methodology for determining the rational parameters of the development system with the injection of rocks from the preparatory workings into the developed space of the working face for the conditions of the d4 seam of PJSC Pokrovskoye Mining Group. The regularity of changes in the width of the rock strip, which is placed in the working space of the face, depending on the cross-sectional area of the preparatory workings and the thickness of the formation, was established.